Effects of rational emotive behavior coaching on occupational stress and work ability among electronics workshop instructors in Nigeria. Issue 19 (May 2017) - Ogbuanya, Theresa C.; Eseadi, Chiedu; Orji, Chibueze T.; Ohanu, Ifeanyi B.; Bakare, Jimoh; Ede, Moses O.
Abstract: Background/objective: This study examined the effectiveness of rational emotive behavior coaching (REBC) on occupational stress and work ability in a sample of electronics workshop instructors in Nigeria. Methods: A pretest–posttest control group design was used. The participants were 108 electronics workshop instructors in technical colleges in the south-east of Nigeria who met the study inclusion criteria. Data were collected using 3 questionnaires and analyzed using a repeated measure analysis of variance and Mann–Whitney U test. Results: REBC led to a significant reduction in occupational stress experienced by the electronics workshop instructors in the REBC group compared to their counterparts in the waitlist control group. Furthermore, the scores for occupation-related irrational beliefs of the instructors in the REBC group were significantly lower than those in the waitlist control group at the end of the coaching intervention. The work ability of the REBC group was significantly better than that of the waitlist control group. Finally, the effects in the REBC group were significantly sustained at 3-month follow-up. Conclusion: REBC is a time-efficient and solution-focused therapeutic modality for assisting occupationally stressed employees in a Nigerian setting. REBC can be used for improving and maintaining work ability of workers. The researchers hope that occupational health professionals and health counselors would extend this approach to tackle psychological issues limiting employees' effectiveness and performance in the Nigerian work environment and in other countries.